2016
DOI: 10.5603/gp.2016.0094
|View full text |Cite
|
Sign up to set email alerts
|

Personality type, social support and other correlates of risk for affective disorders in early puerperium

Abstract: Objectives: The purpose of this study was to assess the prevalence of risk for postpartum mood disorders in mothers during the early postnatal period and to search for coexisting conditions. Material and methods:We studied 546 women in the first week after delivery. The subjects filled out a questionnaire concerning their health, social and demographic status, the Edinburgh Postnatal Depression Scale, the Patient Health Questionnaire, the NEO-FFI Personality Inventory and the Berlin Social Support Scales.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
4
11
0
Order By: Relevance
“…Consistent with some previous research [ 55 , 61 63 ], we further found that more conscientious and more extraverted women experienced fewer depressive and stress symptoms across the peripartum period. Possibly, more conscientious women were characterized by a higher sense of mastery and more effective self-regulation strategies [ 64 , 68 ] and thus managed to adjust to their novel role as a (an expectant) mother more easily.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with some previous research [ 55 , 61 63 ], we further found that more conscientious and more extraverted women experienced fewer depressive and stress symptoms across the peripartum period. Possibly, more conscientious women were characterized by a higher sense of mastery and more effective self-regulation strategies [ 64 , 68 ] and thus managed to adjust to their novel role as a (an expectant) mother more easily.…”
Section: Discussionsupporting
confidence: 92%
“…During pregnancy and after delivery, (expectant) mothers are confronted with manifold changes concerning their body, their family, and their social identity [1][2][3][4]. As suggested by previous research, their personality [54][55][56][57][58][59][60][61][62][63] and levels of perceived social support [5,[69][70][71] might crucially affect how they adjust to these changes and whether they do or do not experience alterations in depressive, anxiety, and stress symptoms across the peripartum period. Psychopathological symptoms and elevated distress during pregnancy and after delivery have been associated with multiple adversities (e.g., an impaired mother-child-relationship) [13][14][15][16][17][18][19][20][21], which in turn have been linked to developmental problems in the offspring [12,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Personality traits such as high neuroticism, low extraversion, and conscientiousness are associated with postpartum disorders (8,9,12,32,33). According to our results, neuroticism is the strongest predictive factor for establishing the probability of PPD, as it was significant in a multivariate logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Having close, supportive ties with others can have a significant positive effect on health, physiological response to psychological stressors (including better functioning of the immune system and reduced cardiovascular reactivity), coping with illness and stress, and promoting longevity (for reviews, see Dickerson & Zoccola, 2011;Uchino, 2006). Researchers have focused on the importance of social support for the functioning of individuals in many contexts of family life associated with stress, such as coping with serious illness and recovering (Luszczynska, Boehmer, Knoll, Schulz, & Schwarzer, 2007;Ogińska-Bulik, 2013;, coping with aging (Acitelli & Antonucci, 1994;Cutrona, Russell, & Rose, 1986), dealing with the consequences of divorce and successfully adjusting to post-divorce life (Amato, 2000;Kołodziej-Zaleska & Przybyła-Basista, 2016), bringing up children with special needs or disabilities (Barnett, Clements, Kaplan-Estrin, & Fialka, 2003;Findler, Jacoby, & Gabis, 2016;Kózka & Przybyła-Basista, 2018), and functioning of women during pregnancy and the postpartum period (Dunkel-Schetter, Sagrestano, Feldman, & Killingsworth, 1996;Ilska & Przybyła-Basista, 2017;Maliszewska, Bidzan, Świątkowska, & Preis, 2016;Rini, Dunkel-Schetter, Hobel, Glynn, & Sandman, 2006;Negron, Martin, Almog, Balbierz, & Howell, 2013). In all these contexts of overcoming life's hardships, social support can prove crucial for ensuring health and well-being, as well as finding effective ways of coping with stress.…”
Section: Introductionmentioning
confidence: 99%